Makna “Bintang Sebagai Alat Pelempar Setan” dalam al-Mulk ayat 5: Studi Interkonektif Tafsir dan Data Astronomis: Studi Interkonektif Tafsir dan Data Astronomis - Nur Fajri Romadhon (Taqaddumi: Journal of Quran and Hadith Studies, 2022)
This paper aims to further explore the meaning of "stars as a tool/weapon throwing demons" contained in several verses of the al-Quran, including al-Mulk verse five. The need for further study of this verse is motivated by the potential contradiction between the meaning of the verse and modern scientific knowledge that is developing today, especially with the science of astronomy. The translation of the word star and its function of throwing demons, is a textual meaning that is not in accordance with the astronomical interpretation of the phenomenon of falling celestial bodies. Because what falls astronomically is not a star, but a meteoroid which is an asteroid debris where this fragment can come from planetary debris or the rest of planet-forming material and sometimes not only from planetary debris but also from satellites and comets. So the question is what is meant by the star in the verse? And what is meant by the demon thrower. In the process, the researcher uses interconnection theory to examine the existing data. With the interconnection theory, it is possible for data that is naqli (religious proposition) to be linked with other data internally -such as the Prophet's hadith, the aṡar of friends of the scholars' opinions-, as well as externally, such as astronomical data regarding the history of meteors and comets. The results of this study indicate that, in terms of the vocabulary used in the verses of the al-Quran, najm, kawkab, and other vocabularies can indeed be interpreted not only as stars in the present sense, but also other celestial bodies, such as meteors and planets. So that only interpreting the vocabulary in stars results in reducing the scope of meaning of the vocabulary itself. In addition, various hadiths that explain al-Mulk verse 5 show that what is meant by a large planet is not the material thrown by the jinn who tap the sky news, but meteoroids which are asteroid fragments. The use of the word najm is precisely to refute the ignorant myth about meteor showers. So, it is precisely the use of the vocabulary in the verse to expand the Arabic imagination when it comes to celestial bodies. Finally, epistemologically it is necessary to admit that astronomy does not allow to reveal the full meaning of the sentence, because the phenomena of celestial bodies in the Qur'an have several functions, including functions that cannot be understood by human reason.